Wichita blues music in the African American community - O'Connor, Patrick Joseph 1948- (University Press of Mississippi, 2024)
"In conversations on regional blues, the traditions of the Mississippi Delta, the Carolina Piedmont, Chicago, Houston, Memphis, New Orleans, and Los Angeles are frequently lauded. But until now, little attention has been paid to the Midwest, despite the presence and popularity of blues in these heartland communities. Wichita Blues: Music in the African American Community seeks to address this gap in music history by exploring the lively Wichita blues tradition. In interviews with nineteen African American Wichita blues performers, author Patrick Joseph O'Connor reveals the evolution of the blues from the 1930s to the 1960s and beyond. Utilizing twenty-five years of fieldwork, Wichita Blues details the history of performance and camaraderie among the musicians of this often-neglected regional sound. The personal interviews offer unique insight into topics that shape Wichita's sound, including how migration from Oklahoma, Texas, and Arkansas brought varied artists to the area and the ways musical traditions cross racial divides and generations. The artists articulate the poetics of the blues and the diverse regional influences that can be detected in their music. In exploring the Wichita blues tradition, O'Connor traces African American history in Kansas, ranging from the Exoduster movement in the late nineteenth century and minstrel shows across the state to Black cowboys and growing urban African American communities in Topeka and Wichita. Including a foreword by renowned music scholar David Evans, Wichita Blues allows seasoned blues musicians to tell their own stories and paints a picture of the vibrant Black music scene in the city."
Keywords: Geschichte; Musik; Schwarze; Wichita, Kan.; Blues (Music) / Kansas / Wichita / History and criticism; Blues musicians / Kansas / Wichita / Interviews; African American musicians / Kansas / Wichita / Interviews